2020
DOI: 10.3390/biomedicines8090359
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Omics Approach Reveals New Signatures in Obese Allergic Asthmatic Children

Abstract: Background: Asthma is a multifactorial condition where patients with identical clinical diagnoses do not have the same clinical history or respond to treatment. This clinical heterogeneity is reflected in the definition of two main endotypes. We aimed to explore the metabolic and microbiota signatures that characterize the clinical allergic asthma phenotype in obese children. Methods: We used a multi-omics approach combining clinical data, plasma and fecal inflammatory biomarkers, metagenomics, and metabolomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…The BIOASMA data set (Gomez-Llorente et al, 2020) comprises clinical, biochemical, anthropometrical parameters, inflammatory biomarkers, metagenomic and metabolomic data for 46 children (12 girls and 34 boys, aged 4-13 years) with an allergic asthma diagnosed based on the Spanish Guidelines for Asthma Management (GEMA criteria 4.4)- (Moral et al, 2016). The children were also classified into normal-weight (n=13), overweight (n=8) and obese (n=25) according to the age and sexspecific thresholds proposed by Cole et al (2000).…”
Section: Results On Real Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The BIOASMA data set (Gomez-Llorente et al, 2020) comprises clinical, biochemical, anthropometrical parameters, inflammatory biomarkers, metagenomic and metabolomic data for 46 children (12 girls and 34 boys, aged 4-13 years) with an allergic asthma diagnosed based on the Spanish Guidelines for Asthma Management (GEMA criteria 4.4)- (Moral et al, 2016). The children were also classified into normal-weight (n=13), overweight (n=8) and obese (n=25) according to the age and sexspecific thresholds proposed by Cole et al (2000).…”
Section: Results On Real Datamentioning
confidence: 99%
“…Metagenomic data were obtained by 16sRNA barcoding sequencing and the Amplicon sequence variants (ASVs) were normalized by the rarefaction method. Deriving potential biomarkers from this data set represents a real challenge (Gomez-Llorente et al, 2020), given the low sample size and the complexity of the experimental design: two potential conflicting factors (asthma severity and weight classification/status) with three levels each are taken into account and the individuals distribution is significantly unbalanced.…”
Section: Results On Real Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolic characteristics of obese asthma are different from those of lean asthma, and the metabolic spectrum of serum showed that the contents of valine, uric acid, and N-methyl-DL-alanine β-glycerophosphate in serum of obese patients with asthma were higher than those of patients with lean asthma, while the contents of asparagine 1 and D-glyceric acid were decreased [ 41 ]. Furthermore, a recent study suggested that the relative proportion of acetic acid in obese children with asthma was significantly lower than in children with normal weight asthma [ 42 ]. The difference in the pathway of bioenergy metabolism between thin and obese asthmatic patients is partly due to the different sensory effects of NO signals [ 43 ].…”
Section: Integrative Analysis Of Asthma-related Metabolites and Metabolic Pathways In Different Samplesmentioning
confidence: 99%
“…In addition, a noteworthy approach involving metagenomics, metabolomics and proteomics data from the BIOASMA cohort (n = 46) has provided important insights regarding obesity-related characteristics in asthmatic children with persistent or episodic asthma [174]. Patients were stratified based on the frequency and severity of the disease as groups of occasional, frequent or persistent asthmatics.…”
Section: Microbiome and Host Metabolome/proteome Data Integrationmentioning
confidence: 99%